2020
DOI: 10.1002/mgg3.1348
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alteration of colorectal adenoma‐carcinoma sequence among gastric adenocarcinoma and dysplastic lesions in a patient with attenuated familial adenomatous polyposis

Abstract: Background Familial adenomatous polyposis (FAP) is characterized by colorectal polyposis and adenocarcinoma that is frequently accompanied by extracolonic neoplasm. The risk of gastric carcinoma is increasing in Western FAP patients as well as Asian patients. Methods We report the case of an FAP patient with fundic gland polyposis who developed gastric adenocarcinoma and metachronous pyloric gland adenomas. These tumors were endoscopically resected, and immunohistochemistry with gastric mucin (i.e., MUC6, MUC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Some reports have suggested the involvement of the colonic adenoma-carcinoma sequence in FAP-associated gastric carcinogenesis. [ 13 , 31 ] In the present study, among 12 gastric adenomas associated with fundic gland polyposis, 4 (33%) increased in size during the observation period. Therefore, it is important to select an appropriate treatment strategy that considers the possibility of carcinogenesis.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Some reports have suggested the involvement of the colonic adenoma-carcinoma sequence in FAP-associated gastric carcinogenesis. [ 13 , 31 ] In the present study, among 12 gastric adenomas associated with fundic gland polyposis, 4 (33%) increased in size during the observation period. Therefore, it is important to select an appropriate treatment strategy that considers the possibility of carcinogenesis.…”
Section: Discussionsupporting
confidence: 51%
“…The gastric cancers in this study showed mixed or intestinal phenotypes, with no gastric-type cancers. Previous case reports have described gastric adenocarcinomas arising from fundic gland polyposis [11,28–31] independent of H pylori infection. It is unclear whether gastric adenomas in patients with FAP confer an increased risk of carcinogenesis through the adenoma-carcinoma sequence.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the genetic alterations of the lesions in a previous report[ 13 ]. In brief, genomic DNA was isolated from formalin-fixed paraffin embedded (FFPE) specimens using a GeneRead DNA FFPE kit (Qiagen, Hilden, Germany).…”
Section: Case Presentationmentioning
confidence: 99%